Investigation on the BER performance of downlink JT-CoMP-NOMA with different modulation schemes - Norshidah Katiran; Shaharil Mohd Shah; Noorsaliza Abdullah; Aimi Syamimi Abdul Ghaffar; Faiz Asraf Saparudin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The principle of joint transmission coordinated multipoint with non-orthogonal multiple access (JT-CoMP-NOMA) is to allow multiple cells in the network to cooperatively transmit data to users using the same network resources in frequency and time domains. The approach would be beneficial in enhancing the system performance in the context of spectral efficiency. This paper presents the performance comparison of JT-CoMP-NOMA for several modulation schemes including QPSK, 16-QAM and 64 QAM in downlink transmission in the context of bit error rate. We conduct an investigation to compare the error performance of JT-CoMP-NOMA with NOMA system. Our simulation results demonstrate that the JT-CoMP-NOMA provides lower bit error rate compared to NOMA system.